Game theory-based malware propagation model for wireless sensor network - Haiping ZHOU; Shigen SHEN; Longjun HUANG; Sheng FENG (Dianxin kexue)
Malware propagation is an important security problem faced by wireless sensor network (WSN).From the perspective of game theory,the microscopic mechanism of malware propagationin WSN was analyzed.The attack-defense game model of WSN was built,and the mixed Nash equilibrium solution of the model was obtained.With the solution,the infection probability of malware was determined and the theoretical model for the malware propagation in WSN was established.Meanwhile,a cellular automata model was proposed to simulate malware propagation process in WSN.Simulation experiments reveal the relationship between the propagation speed and the game parameters.The results of this study are of significance for people to formulate measures to reduce the propagation speed of malware.